Pengaruh Konsep Diri dan Kedisiplinan terhadap Prestasi Belajar Ilmu Pengetahuan Alam - Sarini Dewi Setia (STIKes Ibnu Sina Ajibarang, 2024)
The Influence of Self-Concept and Discipline on Natural Science Learning Achievement. The aim of this study was to determine: 1) The combined influence of self-concept and discipline on the learning achievement of Natural Science among junior high school students in West Jakarta. 2) The influence of self-concept on the learning achievement of Natural Science among junior high school students in West Jakarta. 3) The influence of discipline on the learning achievement of Natural Science among junior high school students in West Jakarta. The research method used was correlational survey. The sample used in this study consisted of 98 students from junior high schools in West Jakarta. The results of the study concluded that 1) There is a significant combined influence of self-concept and discipline on the learning achievement of Natural Science among junior high school students in West Jakarta. This is evidenced by the significance value (sig.) = 0.000 < 0.05 and F-value = 24.849. 2) There is a significant influence of self-concept on the learning achievement of Natural Science among junior high school students in West Jakarta. This is evidenced by the significance value (sig.) = 0.000 < 0.05 and t-value = 6.245. 3) There is a significant influence of discipline on the learning achievement of Natural Science among junior high school students in West Jakarta. This is evidenced by the significance value (sig.) = 0.001 < 0.05 and t-value = 3.541.